Alternative instrument for the evaluation of handgrip strength in Duchenne muscular dystrophy - Mariana Angélica de Souza; Edson Zangiacomi Martinez; Elisângela Aparecida da Silva Lizzi; Ananda Cezarani; Gabriela Barroso de Queiroz Davoli; Marjory Irineu Bená; Cláudia Ferreira da Rosa Sobreira; Ana Claudia Mattiello-Sverzut (BMC, 2022)
Abstract Background The commonly used dynamometers can be ineffective in evaluating handgrip in patients with Duchenne muscular dystrophy (DMD), especially children with generalized muscle weakness. The aim of this study was to analyze whether the modified sphygmomanometer is an effective instrument for handgrip strength evaluation in patients with DMD, during different stages of the disease. Method The handgrip strength of 33 patients was evaluated by the Jamar dynamometer and the modified sphygmomanometer. Motor function was evaluated by the Motor Function Measurement (MFM) scale. Four evaluations, with a six-month interval between each, were performed: Evaluation 1 (N = 33), Evaluation 2 (N = 24), Evaluation 3 (N = 15), and Evaluation 4 (N = 8). A linear regression model with mixed effects was used for the longitudinal data and descriptive analysis of strength for all four evaluations. Result The first evaluation data presented very high correlations between the dynamometer and the modified sphygmomanometer (r = 0.977; p < 0.001). The longitudinal analysis showed a significant difference between Evaluation 1 and the other handgrip strength evaluations obtained using the dynamometer (p < 0.05) but not the modified sphygmomanometer (p > 0.05). Null values were obtained only when using the dynamometer device. Conclusion The modified sphygmomanometer seems to be more suitable than the dynamometer for measuring handgrip strength in all stages of DMD.